A Macrolevel Study of Police Killings at the Intersection of Race, Ethnicity, and Gender - Gaston, Shytierra (Crime & delinquency, 2021)
We investigate macrolevel sources of police use of fatal force at the intersection of race, ethnicity, and gender. Focusing on 580 U.S. counties from 2013 to 2018, we build a unique dataset and analyze whether violent crime, social disorganization, and racial conflict indicators predict police killings among six victim subgroups of Black, Hispanic, and White men and women. Regression results show that violent crime—and social disorganization, albeit less consistently—is positively associated with police killings of men, irrespective of race/ethnicity, and Hispanic women while having no significant impact on Black or White women. We find nuanced evidence that racial conflict shapes police use of fatal force across all six racial-ethnic-gender subgroups. We conclude by discussing the implications of our findings.